2013
DOI: 10.1371/journal.pone.0080135
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans Aging Is Modulated by Hydrogen Sulfide and the sulfhydrylase/cysteine Synthase cysl-2

Abstract: Exogenous hydrogen sulfide (H2S) administration and endogenous H2S metabolism were explored in the nematode C. elegans. Chronic treatment with a slow-releasing H2S donor, GYY4137, extended median survival by 17-23% and increased tolerance towards oxidative and endoplasmic reticulum (ER) stress. Also, cysl-2, a sulfhydrylase/cysteine synthase in C. elegans, was transcriptionally upregulated by GYY4137 treatment and the deletion of cysl-2 resulted in a significant reduction in lifespan which was partially recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 57 publications
3
31
0
Order By: Relevance
“…Loss of RtcB reduces lifespan under conditions of constant ER stress. As previously reported, wild-type animals had shortened life spans when grown on tunicamycin ( Fig 2B) [22]. RtcB mutants A tRNA halves accumulate in RtcB mutants (red arrowheads).…”
Section: Introductionsupporting
confidence: 83%
“…Loss of RtcB reduces lifespan under conditions of constant ER stress. As previously reported, wild-type animals had shortened life spans when grown on tunicamycin ( Fig 2B) [22]. RtcB mutants A tRNA halves accumulate in RtcB mutants (red arrowheads).…”
Section: Introductionsupporting
confidence: 83%
“…Another study found that aged healthy mice have high levels of CBS and suggested that maintenance (and increase) of CBS levels may sustain cortical function, preclude neuronal loss, and extend survival (Bruintjes et al , 2014). Other studies have corroborated their suggestions, finding that H2S prolonged survival in C. elegans (Qabazard et al , 2013; Qabazard et al , 2014). Consequently, modulation of H2S may be a viable strategy to maintain mitochondrial function and improve outcomes in aging individuals exposed to hypoxic ischemic injury.…”
Section: Pharmacologic Therapiesmentioning
confidence: 52%
“…NaHS and PDTC attenuated apoptosis in HUVECs, which is a key process in ED during the development of AS. Consistent with this, Qabazard et al (49) demonstrated that supplementation with GYY4137 markedly decreased oxidative stress-induced overexpression of CHOP, GRP78 and caspase-12 in endothelial cells. In addition, this study demonstrated that p38 mitogen-activated protein kinases (MAPK) demonstrated a key role in the regulation of AngII-induced ED (49).…”
Section: A B C Dmentioning
confidence: 62%